Sporadic Creutzfeldt–Jakob Disease MM1+2C and MM1 are Identical in Transmission Properties. (4th June 2015) - Kobayashi, Atsushi; Matsuura, Yuichi; Iwaki, Toru; Iwasaki, Yasushi; Yoshida, Mari; Takahashi, Hitoshi; Murayama, Shigeo; Takao, Masaki; Kato, Shinsuke; Yamada, Masahito; Mohri, Shirou; Kitamoto, Tetsuyuki
Abstract: The genotype (methionine, M or valine, V) at polymorphic codon 129 of the PRNP gene and the type (1 or 2) of abnormal prion protein in the brain are the major determinants of the clinicopathological features of sporadic Creutzfeldt–Jakob disease (CJD), thus providing molecular basis for classification of sporadic CJD, that is, MM1, MM2, MV1, MV2, VV1 or VV2. In addition to these "pure" cases, "mixed" cases presenting mixed neuropathological and biochemical features have also been recognized. The most frequently observed mixed form is the co‐occurrence of MM1 and MM2, namely MM1+2. However, it has remained elusive whether MM1+2 could be a causative origin of dura mater graft‐associated CJD (dCJD), one of the largest subgroups of iatrogenic CJD. To test this possibility, we performed transmission experiments of MM1+2 prions and a systematic neuropathological examination of dCJD patients in the present study. The transmission properties of the MM1+2 prions were identical to those of MM1 prions because MM2 prions lacked transmissibility. In addition, the neuropathological characteristics of MM2 were totally absent in dCJD patients examined. These results suggest that MM1+2 can be a causative origin of dCJD and causes neuropathological phenotype similar to that of MM1.